On “moving pictures”, or the history of the film thought for all - Ples, Marta (Folia Philosophica, 2009)
Review of the book by Alicja Helman and Jacek Ostaszewski: History of Film Thought. Textbook. Gdańsk: Słowo/obraz/terytoria Publishing House, 2007.